2009
DOI: 10.1152/ajpendo.90599.2008
|View full text |Cite
|
Sign up to set email alerts
|

Berberine suppresses proinflammatory responses through AMPK activation in macrophages

Abstract: Jeong HW, Hsu KC, Lee J-W, Ham M, Huh JY, Shin HJ, Kim WS, Kim JB. Berberine suppresses proinflammatory responses through AMPK activation in macrophages. Am J Physiol Endocrinol Metab 296: E955-E964, 2009. First published February 10, 2009 doi:10.1152/ajpendo.90599.2008 has been shown to improve several metabolic disorders, such as obesity, type 2 diabetes, and dyslipidemia, by stimulating AMP-activated protein kinase (AMPK). However, the effects of BBR on proinflammatory responses in macrophages are poorly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
306
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(331 citation statements)
references
References 53 publications
16
306
0
5
Order By: Relevance
“…and JNK phosphorylation in LPS-stimulated macrophages by activating AMP-activated protein kinase (Jeong et al, 2009). Thus, it will be of interest to further examine whether coptisine activates AMPK to suppress inflammatory responses in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…and JNK phosphorylation in LPS-stimulated macrophages by activating AMP-activated protein kinase (Jeong et al, 2009). Thus, it will be of interest to further examine whether coptisine activates AMPK to suppress inflammatory responses in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] AMPK activation also helps attenuate inflammatory responses in a variety of cell types. 17,[48][49][50] It has been reported that an AMPK activator, AICAR, attenuates the renal hypertrophy, urine H 2 O 2 , and urine and renal MCP-1 in high-fat-dietinduced obese mice. 51 AICAR also abrogates the MCP-1 induction by palmitic acid in cultured mesangial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of AMPK using pharmacological ligands has been demonstrated to induce anti-inflammatory and immunosuppressive effects in a variety of cell types, and thus is potentially useful in the treatment of various diseases (7,8,16,17). A study has shown that activation of the AMPK signaling pathway by 5-aminoimidazole-4-carbox amide-1-β-D-ribofuranoside and berberine ameliorates the LPS-induced mice model of ALI (11).…”
Section: A B Cmentioning
confidence: 99%